Integral Fungsi Hiperbolik - Mutiara Nursandi (PT PUSTAKA CENDEKIA GROUP, 2024)
Certain combinations of exponential functions will form hyperbolic functions such as hyperbolic sine (sinh), hyperbolic cosine (cosh), hyperbolic tangent (tanh⁡), hyperbolic secant (sech⁡), hyperbolic cosecant (csch⁡) and hyperbolic cotangent (coth⁡). An exponential function is a function usually denoted in the form where is an irrational real number with value … The integral of a hyperbolic function is the anti-derivative of a hyperbolic function like , .